The Effectiveness Personal Data Protection of Financial Technology Consumers by Financial Services Authority in Islamic Law Perspective - Ita Wardatul Jannah; Burhanuddin Susamto (Journal of Islamic Business Law, 2017)
This research intends to describe the effectiveness of personal data protection of financial technology consumers by the Jakarta Financial Services Authority reviewed base on Islamic law. This research uses empirical legal research method with socio legal approach also data collection are interview and docummentation study. The result of research clarify that the personal data protection of financial technology consumers by Jakarta Finacial Services Authority through regulations, coaching, and socialization (preventive), also efforts to resolve disputes (respressive). The both are ineffective. There are no clear legal substance regarding the retention period of consumers’ personal data stroge and dispute resolution’s flow to victims’ losses. The legal substance that not comprehensive raises the role of Jakarta Financial Services Authority as legal structure does not function optimally, as many as 4,493 victims of personal data misuse on financial technology have not obtained legal certainty. Whereas users of financial technology have increasingly become a legal culture of Indonesian people. According to Islamic law, the personal data protection is a honor protection principle (hifzh al-irdh) maqashid syariah at the primary needs level (dharuriyat).